(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Currently, various boxing competitions, tournaments and meetings are being held in Uzbekistan. It is also worth noting that Uzbekistan has found its place in the world of boxing. Despite this, we have to teach the coaches different ways to teach young players. At the same time, it is worth emphasizing how to properly organize self-management.